JAVANESE CULTURAL VALUES IN THE SHORT FILM TOPI-TINDAK TANDUK SUBASITA AND ITS RELEVANCE IN BIPA LEARNING - Safitri, Paramita Ida; Muliastuti, Liliana; Mayuni, Ilza (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to analyze the Javanese cultural values presented in the short film Topi-Tindak Tanduk Subasita, and to relate their relevance to BIPA learning. Short films, as visual representations of culture, have great potential to present authentic and meaningful socio cultural contexts in second language learning processes. This study uses a qualitative descriptive method with a cultural discourse analysis approach and language politeness theory to interpret the characters dialogues, expressions, and actions. The Javanese cultural values studied in this research focus on two things, namely: a) Javanese philosophical teachings; b) politeness values. The results of the study indicate that this short film displays Javanese cultural values reflected in the concepts of unggah-ungguh basa (language politeness), andhap asor (polite or humble attitude), and empan papan (ability to position oneself or appropriate attitude). These Javanese cultural values are not only expressed through speech but also through body language and the structure of social interaction between characters. In the context of BIPA learning, these values are relevant because they can equip BIPA learners with intercultural understanding, increase pragmatic awareness, and teach contextual language use in accordance with the social norms of Indonesian society, especially Javanese society.